2021
DOI: 10.1155/2021/6627979
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaemia and Its Associated Factors among Type 2 Diabetes Mellitus Patients in University of Gondar Comprehensive Specialized Hospital

Abstract: Background. Anaemia is one of the commonest blood disorders seen in patients with diabetes. In Ethiopia, chronic illnesses are tremendously raising with their complications. But very little research has been conducted, particularly on anaemia among diabetes mellitus (DM) patients. Therefore, this study aimed at assessing the prevalence of anaemia and associated factors among type 2 diabetes mellitus patients in Northwest Ethiopia. Methods. A cross-sectional study design was employed at University of Gondar Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
3
12
3
Order By: Relevance
“…On the other hand, the current prevalence was low compared to the findings reported in Brazil (34.2%), Ethiopia (30.2%), and Pakistan (63%) [ 27 , 40 , 41 ]. In contrast, this finding was high compared to the result found in Eastern Ethiopia (20.1%), and Gondar, Ethiopia (8.06%) among T2DM patients [ 42 , 43 ]. In diabetess, prolonged exposure to hyperglycaemia is directly associated with cardiovascular disease and renal disease.…”
Section: Discussioncontrasting
confidence: 64%
“…On the other hand, the current prevalence was low compared to the findings reported in Brazil (34.2%), Ethiopia (30.2%), and Pakistan (63%) [ 27 , 40 , 41 ]. In contrast, this finding was high compared to the result found in Eastern Ethiopia (20.1%), and Gondar, Ethiopia (8.06%) among T2DM patients [ 42 , 43 ]. In diabetess, prolonged exposure to hyperglycaemia is directly associated with cardiovascular disease and renal disease.…”
Section: Discussioncontrasting
confidence: 64%
“…23,24 The finding of this study was similar to a previous study in Gondar by Kebede et al where the magnitude of anemia was 8.06%. 25 However, it is lower than studies conducted in Debre Berhan (20.1%) 26 and Debre Tabor (29.81%) 27 that reported a higher magnitude of anemia than the current study. In general, a systematic review and meta-analysis conducted by Adane et al showed that the overall magnitude of anemia was 31.12% (95% CI; 9.66, 52.58) in DM patients.…”
Section: Dovepresscontrasting
confidence: 83%
“…Nine published studies were included in this systematic review and meta‐analysis to estimate the pooled prevalence of anaemia in DM patients. The minimum and maximum prevalence of anaemia were 8.06% and 34.8% in Gondar 23 and Harari, 27 respectively. The overall pooled prevalence of anaemia in DM patients using the random effects model was 22.11% (95% CI: 15.83–28.39) I 2 = 94.8%.…”
Section: Resultsmentioning
confidence: 91%
“…Three regional states (provinces) of Ethiopia were represented in the studies: six studies were conducted in Amhara, [20][21][22][23][24][25] 1 study in Tigray, 26 and 2 study in Oromo regional state. 27 Six studies [21][22][23][24]26,28 had used a systematic sampling strategy while the other 3 studies 20,27 used a simple random sampling to select their representative sample. The mean age of study participants ranged from 40 to 56.3 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation